Candiduria in high-risk patients and its antifungal susceptibility testing - Shetty, Mayuri P.; Bhakre, Jayshree B.; Iravane, Jyoti A. (International Journal of Research in Medical Sciences, 2024)
Background: Candida is part of the natural microbiota of an individual’s mouth cavity, gastrointestinal system, and vagina. Candida species are of clinical importance because they are the most common cause of nosocomial urinary tract infections (UTIs), oral candidiasis, and genitourinary candidiasis. The presence of budding yeast cells in urine can be a sign of extensive candidiasis, urinary tract infections, or sample contamination. It is necessary to confirm the presence of yeast cells in a fresh urine sample to differentiate contamination from colonization or infection. Numerous antifungals are available to treat candida infections. Over the last few decades, there has been an increase in antifungal resistance, especially against non-albican species. Methods: A hospital-based retrospective observation study was conducted over 12 months, from January 2023 to December 2023 in department of microbiology at Government Medical College and Hospital Aurangabad (Chhatrapati Sambhajinagar), Maharashtra. A total of 2434 samples were received and processed according to standard operating procedures. Results: A total of 38 (26.76%) C. albicans and 104 (73.23%) non-albicans species were isolated from 142 urine samples. C. tropicalis was the most frequently isolated Candida species (52.11%) from urine cultures, followed by C. albicans (26.76%), C. glabarata (8.45%), C. parapsillosis (7.04%), C. krusei (2.8%), and C. guilliermondii (2.8%). All Candida species were maximally susceptible to fluconazole, itraconazole, caspofungin, and voriconazole as compared to amphotericin B and ketoconazole. Conclusions: The finding of candiduria in a patient with or without symptoms should be neither neglected nor hastily managed but requires a careful evaluation that should proceed in a logical manner.